2009
DOI: 10.1124/dmd.108.026211
|View full text |Cite
|
Sign up to set email alerts
|

Protein Electrophile-Binding Motifs: Lysine-Rich Proteins Are Preferential Targets of Quinones

Abstract: ABSTRACT:Quinones represent an important class of endogenous compounds such as neurotransmitters and coenzyme Q10, electrophilic xenobiotics, and environmental toxicants that have known reactivity based on their ability to redox cycle and generate oxidative stress, as well as to alkylate target proteins. It is likely that topological, chemical, and physical features combine to determine which proteins become targets for chemical adduction. Chemical-induced post-translational modification of certain critical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…This, however, was not surprising due to the fact that the sequence of this enzyme does not contain any of the lysine motifs previously identified in other proteins as being reactive with quinones. 62,63 …”
Section: Discussionmentioning
confidence: 99%
“…This, however, was not surprising due to the fact that the sequence of this enzyme does not contain any of the lysine motifs previously identified in other proteins as being reactive with quinones. 62,63 …”
Section: Discussionmentioning
confidence: 99%
“…Recently, Labenski et al showed that lysine-rich regions of proteins promote adduct formation with electrophilic quinones [55]. As more is discovered about specific electrophile-responsive proteomes, additional electrophile binding motifs may be discovered.…”
Section: Introductionmentioning
confidence: 99%
“…However, phenoxyl radicals can also be formed in non-enzymatic reactions via polyphenol auto-oxidation in the presence of oxygen radicals, H 2 O 2 and metal ions [29], [30]. The phenoxyl radicals (semi-quinones and quinone radicals) can spontaneously react with nucleophilic groups of amino acids and proteins, such as the epsilon amino group of lysine or the sulfhydryl group of cysteine, forming stable, covalent bonds [31], [32]. The examples of protein complexation by quinones relate to melanin formation [33], melanization and sclerotization of insect cuticle [34], [35] and lignin biosynthesis in plants [36][38].…”
Section: Introductionmentioning
confidence: 99%